Production Biotechnology with Controlled Environmental Regimes, Substrates and Enzyme Markers for the Shiitake Mushroom, Lentinula Edodes - Krishnen, Ganisan (2001)
Mycelial growth of L. edodes was optimum at 25°C in six of the seven strains of L. edodes tested. Mycelial biomass production was greater on sawdust than grain with 0.53 to 1.60 mg glucosamine per 200 g substrate derived from sawdust compared to 0.02 to 0.2 mg glucosamine per 200 g from grain. In fructification, a fluctuating temperature set of 15°C (8 h)/25°C (16 h), with continuous lighting at 25- 35 lux, humidity of 80-95% and aeration of 1.3-2.5 m/s produced the highest yield or Biological Efficiency (RE.) in 11 of the 13 strains tested at three temperature sets. Strains L38 (7.1-32.7% B.E.) and L300 (7.2-35.5% RE.) were the best yield producers at all three temperature sets. Mycelial density during spawn-run was found to be uncorrelated with yield in the 13 strains tested. In the present study, specific activities of three lignocellulolytic enzymes, laccase, carboxymethylcellulase (CMC'ase) and xylanase indicated that the second week and 17th week· was the correct time to initiate fruiting on liquid and rubber sawdust medium respectively.